Freedom as Resistance in Scotland (Presses universitaires de Franche-Comté, 2026)
Echoing the reputed characteristics of their national emblems, the attractive flower of the thistle, the strength of the wild cat, the fearlessness of the unicorn, and their cautionary motto Nemo me impune lacessit, the Scots frequently call on their spirit of resistance. This volume explores Scotland’s culture of resistance through history and as expressed in political and social manners, in literature and drama, and in the media. It proposes ten perspectives dealing with the double concepts of Scottish national expressions of freedom and dissent as a way of upholding Scottishness within the British and European contexts, from the Middle Ages to today.